2003
DOI: 10.1074/jbc.m302518200
|View full text |Cite
|
Sign up to set email alerts
|

TWEAK Mediates Signal Transduction and Differentiation of RAW264.7 Cells in the Absence of Fn14/TweakR

Abstract: Tumor necrosis factor-like weak inducer of apoptosis (TWEAK) is a member of the tumor necrosis factor family that is implicated in apoptosis, proliferation, migration, and inflammation. We describe our findings showing that TWEAK mediated the differentiation of RAW264.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
111
2
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 36 publications
4
111
2
1
Order By: Relevance
“…Polek et al (46) reported that TWEAK can induce differentiation into osteoclasts of RAW cells that reportedly do not display the Fn14 receptor. As no other TWEAK receptor has been demonstrated to date, this observation may be explained by the recent finding by De Ketelaere et al (47) that soluble TWEAK can internalize into several cell lines (not via Fn14) and translocate directly to the nucleus, leading to nuclear translocation of GSK-3␤ and p65 and induction of NF-B-driven gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Polek et al (46) reported that TWEAK can induce differentiation into osteoclasts of RAW cells that reportedly do not display the Fn14 receptor. As no other TWEAK receptor has been demonstrated to date, this observation may be explained by the recent finding by De Ketelaere et al (47) that soluble TWEAK can internalize into several cell lines (not via Fn14) and translocate directly to the nucleus, leading to nuclear translocation of GSK-3␤ and p65 and induction of NF-B-driven gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, whereas both soluble TWEAK and memTWEAK are strong stimuli of the alternative NF-kB pathway, only memTWEAK also efficiently triggers the classical NF-kB pathway (24). Several members of the TNFR-associated factor (TRAF) family and Rac1 have been identified as Fn14-interacting molecules, but their relevance for defined aspects of Fn14 signal transduction is poorly understood (25)(26)(27). In molecular terms the best elucidated Fn14 signaling event is presumably TRAF2 recruitment and its relevance for alternative NFkB signaling (28).…”
mentioning
confidence: 99%
“…TWEAK is widely expressed in many tissues including heart, skeletal muscle, and kidney (11,14). Binding of TWEAK to its receptor, Fn14 (13), mediates multiple biologic effects such as cellular growth, proliferation, and migration; osteoclastogenesis; angiogenesis; and apoptosis (15)(16)(17). sTWEAK plasma levels decrease with impaired renal function and associate with the aggravation of the endothelial function and the mortality risk (18,19).…”
mentioning
confidence: 99%